Changes in the colon microbiota and intestinal cytokine gene expression following minimal intestinal surgery - Lapthorne, Susan (World J Gastroenterol, 2015)
AIM: To investigate the impact of minor abdominal surgery on the caecal microbial population and on markers of gut inflammation. METHODS: Four week old piglets were randomly allocated to a no-surgery “control” group (n = 6) or a “transection surgery” group (n = 5). During the transection surgery procedure, a conventional midline incision of the lower abdominal wall was made and the small intestine was transected at a site 225 cm proximal to the ileocaecal valve, a 2 cm segment was removed and the intestine was re-anastomosed. Piglets received a polymeric infant formula diet throughout the study period and were sacrificed at two weeks post-surgery. Clinical outcomes including weight, stool consistency and presence of stool fat globules were monitored. High throughput DNA sequencing of colonic content was used to detect surgery-related disturbances in microbial composition at phylum, family and genus level. Diversity and richness estimates were calculated for the control and minor surgery groups. As disturbances in the gut microbial community are linked to inflammation we compared the gene expression of key inflammatory cytokines (TNF, IL1B, IL18, IL12, IL8, IL6 and IL10) in ileum, terminal ileum and colon mucosal extracts obtained from control and abdominal surgery groups at two weeks post-surgery. RESULTS: Changes in the relative abundance of bacterial species at family and genus level were confined to bacterial members of the Proteobacteria and Bacteroidetes phyla. Family level compositional shifts included a reduction in the relative abundance of Enterobacteriaceae (22.95 ± 5.27 vs 2.07 ± 0.72, P < 0.01), Bacteroidaceae (2.54 ± 0.56 vs 0.86 ± 0.43, P < 0.05) and Rhodospirillaceae (0.40 ± 0.14 vs 0.00 ± 0.00, P < 0.05) following transection surgery. Similarly, at the genus level, changes associated with transection surgery were restricted to members of the Proteobacteria and Bacteroidetes phyla and included decreased relative abundance of Enterobacteriaceae (29.20 ± 6.74 vs 2.88 ± 1.08, P < 0.01), Alistipes (4.82 ± 1.73 vs 0.18 ± 0.13, P < 0.05) and Thalassospira (0.53 ± 0.19 vs 0.00 ± 0.00, P < 0.05). Surgery-associated microbial dysbiosis was accompanied by increased gene expression of markers of inflammation. Within the ileum IL6 expression was decreased (4.46 ± 1.60 vs 0.24 ± 0.06, P < 0.05) following transection surgery. In the terminal ileum, gene expression of TNF was decreased (1.51 ± 0.13 vs 0.80 ± 0.16, P < 0.01) and IL18 (1.21 ± 0.18 vs 2.13 ± 0.24, P < 0.01), IL12 (1.04 ± 0.16 vs 1.82 ± 0.32, P < 0.05) and IL10 (1.04 ± 0.06 vs 1.43 ± 0.09, P < 0.01) gene expression increased following transection surgery. Within the colon, IL12 (0.72 ± 0.13 vs 1.78 ± 0.28, P < 0.01) and IL10 (0.98 ± 0.02 vs 1.95 ± 0.14, P < 0.01) gene expression were increased following transection surgery. CONCLUSION: This study suggests that minor abdominal surgery in infants, results in long-term alteration of the colonic microbial composition and persistent gastrointestinal inflammation.